Towards an immersive virtual environment for physics experiments supporting collaborative settings in higher education - Guetl, Christian; Belcher, J.; Scheucher, T.; dos Santos, F.; Bailey, P.; Berger, S. (IGI Global, 2011)
Literature survey on science education suggests the inclusion of interactive exploratory and collaborative learning experiences. However, recent remote laboratories and simulations do not sufficiently support the collaborative component. Thus, this book chapter introduces the development of an immersive virtual environment built on top of OpenWonderland to collaboratively experience remote laboratory experimentation and simulations. Motivated by previous experiences, utilizing iLab-based remote lab and TEAL simulations within MIT’s physics courses, our research project focuses on the enhanced integration of physics phenomena. However, most of the outlined experiences and results are well able to be transferred to other subjects in science education. This book chapter outlines development and findings along the path of our research endeavor so far; it also gives related background knowledge and discusses possible future trends.